The Bile Acid TUDCA Improves Beta-Cell Mass and Reduces Insulin Degradation in Mice With Early-Stage of Type-1 Diabetes - Bronczek, Gabriela Alves; Vettorazzi, Jean Franciesco; Soares, Gabriela Moreira; Kurauti, Mirian Ayumi; Santos, Cristiane; Bonfim, Maressa Fernandes; Carneiro, Everardo Magalhães; Balbo, Sandra Lucinei; Boschero, Antonio Carlos; Costa Júnior, José Maria (Frontiers in Physiology, 2019)
Type 1 diabetes (T1D) is characterized by impairment in beta-cell mass and insulin levels, resulting in hyperglycemia and diabetic complications. Since diagnosis, appropriate control of glycaemia in T1D requires insulin administration, which can result in side effects, such as hypoglycemia. In this sense, some bile acids have emerged as new therapeutic targets to treat T1D and T2D, as well as metabolic diseases. The taurine conjugated bile acid, tauroursodeoxycholic (TUDCA) reduces the incidence of T1D development and improves glucose homeostasis in obese and T2D mice. However, its effects in early-stage of T1D have not been well explored. Therefore, we have assessed the effects of TUDCA on the glycemic control of mice with early-stage T1D. To achieve this, C57BL/6 mice received intraperitoneal administration of streptozotocin (STZ, 40 mg/kg) for 5 days. Once diabetes was confirmed in the STZ mice, they received TUDCA treatment (300 mg/kg) or phosphate buffered saline (PBS) for 24 days. After 15 days of treatment, the STZ+TUDCA mice showed a 43% reduction in blood glucose, compared with the STZ group. This reduction was likely due to an increase in insulinemia. This increase in insulinemia may be explained, at least in part, by a reduction in hepatic IDE activity and, consequently, reduction on insulin clearance, as well as an increase in beta-cell mass and a higher beta-cell number per islet. Also, the groups did not present any alterations in insulin sensitivity. All together, these effects contributed to the improvement of glucose metabolism in T1D mice, pointing TUDCA as a potential therapeutic agent for the glycemic control in early-stage of T1D.